POTENCY OF ENHALUS ACOROIDES FROM INDONESIA REGION FOR HALAL PHARMACEUTICAL INDUSTRY - Ismarti, Ismarti; Amelia, Fitrah (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2023)
Currently, the implementation of the Halal assurance system in Indonesia is mandatory. A side from food, pharmaceutical, cosmetics, and medicines must all be halal certified. Natural products, particularly marine-based products, are an alternative choice for the cosmetics and pharmaceutical industry's raw materials. Enhalus acoroides are common along Indonesia's coasts and have the potential to be used as raw materials in halal cosmetics and pharmaceutical products. The purpose of this paper is to examine the potential of E. acoroides samples collected from various locations in Indonesia in terms of bioactive compounds and their applications. Secondary metabolites namely alkaloids, flavonoids, polyphenols, steroids, triterpenes, and tannins have been reported in E. acoroides extract from Indonesia, and they have the potential to be used as antibacterial, antiaging, antiviral, antitumor, and antioxidant in the pharmaceutical and cosmetic industries in Indonesia